(untitled) (Journal of Applied Learning and Teaching, 2024)
Psychology has largely viewed human functioning from a deficit model in the past but has since turned to a more optimistic, positive psychological lens. Gratitude is a well-researched concept associated with a broad range of psychology theories, such as Fredrickson’s broaden and build theory and Algoe’s find, remind, and bind theory. Research studies revealed that gratitude is one of the strongest predictors of wellbeing and is strongly linked with better psychological and subjective wellbeing. However, gratitude is rarely studied in higher education contexts, making it critical to understand if and how gratitude can impact learners’ wellbeing positively, which, in turn, may lead to better performance in their studies and improvements in their overall wellbeing. This research study employs a qualitative approach, using semi-structured interviews to capture the experiences and perspectives of students and lecturers in higher education in relation to gratitude. Findings revealed that gratitude leads to positive emotions, better relationships, and prosocial behaviours. Additionally, gratitude was found to improve students’ wellbeing and increase their engagement and motivation levels towards learning. To integrate gratitude into the academic curriculum, discourses surrounding gratitude must be reconsidered, and intentional learning spaces for gratitude should also be developed.